Productivity and quality-related traits of wheat germplasm affected by heat stress - Vahid Rezaei; Mohammad Mahdi Majidi; Aghafakhr Mirlohi; Ghodratollah Saeidi (PLoS ONE, 2026)
Heat stress (HS) significantly impedes wheat production, making the development of heat-tolerant cultivars increasingly essential in the context of climate change. This study evaluated 153 elite spring wheat ( Triticum aestivum L.) genotypes from the Wheat Association Mapping Initiative (WAMI) panel and three controls in field trials conducted during the 2020–2021 and 2021–2022 growing seasons at the Isfahan University of Technology research farm, Iran. Two sowing dates (SD; fall and spring) under full irrigation were employed to replicate HS conditions, with spring SD simulating terminal HS and reflecting regional farming practices. HS reduced days to flowering (DF), anthesis (DA), and maturity (DM) by 36–45%, shortened the grain-filling period (GFP), and decreased grain yield (GY) by ~25%, while key flour-quality traits (e.g., Zeleny index and grain hardness) remained stable under both SDs. Considerable genotypic variability was observed in both agronomic and quality traits. Stress tolerance and sensitivity indices (STI, MP, YSI, and HSI) were used to classify genotypes, with HSI identified as the most effective index due to its strong association with yield performance under HS. Several WAMI lines (e.g., 029, 123, 104, 067, and 139) demonstrated high yield potential combined with robust heat tolerance, as evidenced by their reduced yield loss under HS. These findings highlight the value of the WAMI panel for identifying heat-resilient wheat genotypes and providing critical insights for breeding programs targeting improved wheat performance under terminal HS and water-limited environments.